Multiparametric MRI in Biopsy Guidance for Prostate Cancer: Fusion-Guided - Rothwax, Jason T. (Hindawi Publishing Corporation, 2014)
Prostate cancer (PCa) is the most common solid-organ malignancy among American men and the second most deadly. Current guidelines recommend a 12-core systematic biopsy following the finding of an elevated serum prostate-specific antigen (PSA). However, this strategy fails to detect an unacceptably high percentage of clinically significant cancers, leading researchers to develop new, innovative methods to improve the effectiveness of prostate biopsies. Multiparametric-MRI (MP-MRI) has emerged as a promising instrument in identifying suspicious regions within the prostate that require special attention on subsequent biopsy. Fusion platforms, which incorporate the MP-MRI into the biopsy itself and provide active targets within real-time imaging, have shown encouraging results in improving the detection rate of significant cancer. Broader applications of this technology, including MRI-guided focal therapy for prostate cancer, are in early phase trials.